Evaluation of potential pseudostems Musa spp. For biomass production (2023)
It is evident that many processes at industrial level are limited by not disposing throughout the time, in a sustainable and continuous way, sources of raw materials of high potential. It is then that the use of foliar residues of Musa spp. plants plays an important role, taking into account that for being a perennial tropical crop, it presents a high production of biomass per unit area annually. It is to remark that on a regular basis, biomass produced is left on plantations after every harvest, which turns to be a problem not only for crop management, but also for the environment. This research evaluated the potential of pseudostem of Musa spp. for biomass production in order to generate added value to its crops and decrease the productiveenvironmental problem that all its waste produce. Plant samples of pseudostem are taken from the villages of San Francisco de Sales, Cundinamarca - Colombia y Tibaná, Boyacá - Colombia. Pseudostem cutting was performed at a distance of 1 m from the base of the stem; the type of cut is transversal and the following 50 cm were used as raw material. With the purpose of identifying the exploitable physicochemical components of the pseudostem of Musa spp, one bromatological analysis was performed - Van Soest for every origin (San Francisco y Tibaná). To carry out the bromatological analysis, it was required 250g of each sample. The parameters evaluated were moisture content (H), ash content, ether extract or crude fat (GC), fiber, protein, carbohydrates, nitrogen - free extract (ELN), minerals, structural and nonstructural composites. A design with factorial arrangement with three replicates per treatment was used. A simple variance analysis (ANOVA) among the means of samples was performed by treatment with a significance level of 95% (a=0,05) in order to establish if there are meaningful differences for the variables in evaluation. In the case of not finding meaningful differences among the samples, a multiple range test was performed using the statistical package Statgraphics Centurion. While conducting the analysis of the study variables for raw materials in fresh, and regardless of their origin, the high potential for biomass production presented by pseudostem of Musa spp was detected, thus presenting a dry biomass content exceeding 70% in both stems. The elements of greater variation in the composition are lignin content, ashes, hemicellulose, nonstructural carbohydrates as well as sodium and manganese. © Copyright 2017, AIDIC Servizi S.r.l.